2022
DOI: 10.1186/s13059-022-02653-7
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and machine learning methods for spatially resolved transcriptomics data analysis

Abstract: The recent advancement in spatial transcriptomics technology has enabled multiplexed profiling of cellular transcriptomes and spatial locations. As the capacity and efficiency of the experimental technologies continue to improve, there is an emerging need for the development of analytical approaches. Furthermore, with the continuous evolution of sequencing protocols, the underlying assumptions of current analytical methods need to be re-evaluated and adjusted to harness the increasing data complexity. To motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 122 publications
0
71
0
Order By: Relevance
“…On the other hand, the LDA, SVM, and logistic regression classifiers were shown to be robust to the perturbation methods in the framework. The developed method is generally intended for use on biological datasets such as RNA expressions, metabolite concentrations, or protein concentration data because these types of datasets involve similar noise characteristics to the ones investigated here [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the LDA, SVM, and logistic regression classifiers were shown to be robust to the perturbation methods in the framework. The developed method is generally intended for use on biological datasets such as RNA expressions, metabolite concentrations, or protein concentration data because these types of datasets involve similar noise characteristics to the ones investigated here [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…We focus on methods specialized for ST data analysis. While a detailed description of all the methods mentioned here is beyond the scope of this review, more detailed descriptions of the ST data analysis methods can be found in the original research articles or the recent reviews [27] , [28] , [29] , [83] , [101] , [102] .
Fig.
…”
Section: Advanced Solutions In the Analysis Of Spatial Transcriptomic...mentioning
confidence: 99%
“…In addition to domain recognition, the enhancement of spatial gene expression data also presents a significant challenge. Though great progress has been made in spatial technologies, the major problems such as missing values, data sparsity, low coverage, and noises 2,15 encountered in spatial transcriptomics profiles are impeding the effective use and the elucidation of biology insights 16,17 . Meanwhile, the multi-channel spatial images in single-cell spatial data consist of high-resolution, high-content features detected in the tissue, such as cell types, functions, and morphologies of cellular compartments, as well as the spatial distributions of cells.…”
Section: Introductionmentioning
confidence: 99%